Modelo conceitual de fluxo dos aquíferos pelíticos-carbonáticos da Região da APA Carste de Lagoa Santa, MG - Rodrigo Sérgio de Paula (2019)
The area studied is 505 km², 35 km north of the city of Belo Horizonte, partially or fully encompassing six municipalities in the Metropolitan Region of Belo Horizonte, and encompasses the 350 km² of the APA Lagoa Santa Karst conservation unit. Despite the natural fragility, the region has been a target of several types of projects, intensifying the consumption of water, especially the underground. This study aimed at the design of a hydrogeological flow model capable of supporting, technically and scientifically, the management of this resource, using hydroestratigraphic architecture characterization, aquifer contour conditions, spatialization of hydraulic parameters and water inputs and ouputs. The local aquifer system belongs to the Bambuí Group, a neoproterozoic group composed of the aquifer limestones of the Sete Lagoas Formation, partially covered by the metapelites constituting the aquitard of the Serra de Santa Helena Formation and Cenozoic coverings. The Sete Lagoas aquifer unit directly overlaps the Gnassic-granitic-migmatitic fissural aquifer of the Belo Horizonte Complex. Carbonate terrains have features of a well-developed karst, notoriously linked to the geological-structural attributes, expressed by an abundance of fractured massifs, sinks, depressions, upwelling / upwelling, ducts, caves, and predominantly subterranean drainage. The superficial and subterranean flows have as destination the Das Velhas river, base level for region. The methods of the study involved: i) the survey of the geological-structural characteristics, elaboration of the water balance by Rutledge and Daniel (1994) with the quantification of the inputs and outputs of the aquifer system; ii) spatialization of hydraulic parameters (K, S, T, Qs) obtained from existing water level recovery data; iii) identification of boundary conditions; iv) relationships between well water intakes and karstic upwellings. It was carried out the installation and monitoring of 7 automated fluviometric stations, hydrological year 2016/2017, and a method based on temporal series correlation was developed to complete the lags of the collected data, obtaining an error less than 10% between the calculated values and monitored. The rainfall, 1010 mm, was obtained in existing stations. The results showed surface response of two days on average and an average basic flow of 91%, evidencing a well-developed karstic system controlled by groundwater. The aquifer recharge was 11% of the annual precipitation of 1010 mm, in addition to a groundwater port provided by external basins that contributes with a contribution of 26 mm. The contour conditions associated with the lower hydraulic conductivity lithologies and flowing water courses allowed to delimit the studied aquifer unit, to the east by the Das Velhas river, to the southwest and south by the Ribeirão da Mata to the north and northwest by the metapelites of the Serra de Santa Helena Formation. It was identified to the east, in the stream basin of Palmeiras a hydraulic connection with the adjacent area to the region of study. A highly productive, karstic upper compartment was identified above the 638 m elevation, and a lower, less productive karstic-fissural compartment was located below this elevation. The modal values of K obtained were of the order of 10-3m/s and 10-7m/s, respectively, with the flows of the two compartments in the direction of W for E and SW for NE, having as main conditioner the sub-horizontal fractures divers for E.